2003
DOI: 10.1177/0020764003049001537
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Suicide in Slovenia: A Cross-Sectional Survey

Abstract: Results do not allow a general statement whether attitudes towards suicide are permissive or restrictive. However, in the subgroup of respondents with SI we found a tendency towards permissiveness regarding suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
2
12
0
1
Order By: Relevance
“…Similar to our study, most studies from other countries find more accepting attitudes about suicide among those with more education (Salander Renberg & Jacobsson, 2003; Singh, Williams, & Ryther, 1986) so this appears to be a robust relationship cross-nationally. The higher acceptability of suicide among females found in our study is also found in some, but not all, studies from other countries (Agnew, 1998; Beautrais, Horwood, & Fergusson, 2004; Hjelmeland et al, 2008; Joe, Romer, & Jamieson, 2007; Kocmur & Dernovšek, 2003; Parker, Cantrell, & Demi, 1997; Salander Renberg & Jacobsson, 2003; Zemaitiene & Zaborskis, 2005); the finding in China could be related to the relatively high rate of suicide in Chinese females compared to that in other countries (WHO, 2002). Controversy remains about the relationship of age to attitudes about the acceptability of suicide (Salander Renberg et al, 2008; Salander Renberg & Jacobsson, 2003; Segal, Mincic, Coolidge, & O’Riley, 2004); the decreasing acceptability of suicide as individuals age (after adjusting for educational level) found in our study may be a reflection of an underlying culturally conditioned conservatism that results in increasing intolerance to all forms of social deviance (including suicidal behavior) as one ages.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to our study, most studies from other countries find more accepting attitudes about suicide among those with more education (Salander Renberg & Jacobsson, 2003; Singh, Williams, & Ryther, 1986) so this appears to be a robust relationship cross-nationally. The higher acceptability of suicide among females found in our study is also found in some, but not all, studies from other countries (Agnew, 1998; Beautrais, Horwood, & Fergusson, 2004; Hjelmeland et al, 2008; Joe, Romer, & Jamieson, 2007; Kocmur & Dernovšek, 2003; Parker, Cantrell, & Demi, 1997; Salander Renberg & Jacobsson, 2003; Zemaitiene & Zaborskis, 2005); the finding in China could be related to the relatively high rate of suicide in Chinese females compared to that in other countries (WHO, 2002). Controversy remains about the relationship of age to attitudes about the acceptability of suicide (Salander Renberg et al, 2008; Salander Renberg & Jacobsson, 2003; Segal, Mincic, Coolidge, & O’Riley, 2004); the decreasing acceptability of suicide as individuals age (after adjusting for educational level) found in our study may be a reflection of an underlying culturally conditioned conservatism that results in increasing intolerance to all forms of social deviance (including suicidal behavior) as one ages.…”
Section: Discussionsupporting
confidence: 85%
“…2004; Eskin, 2004; Colucci & Martin, 2007; Etzersdorfer, Vijayakumar, Schöny, Grausgruber, & Sonneck, 1998; Gibb et al, 2006; Joe et al . 2007; Kocmur & Dernovšek, 2003; Salander Renberg & Jacobsson, 2003; Stein, Brom, Elizur, & Witztum, 1998; Stein et al, 1992; Zemaitiene & Zaborskis, 2005), but some studies find no clear association between attitude changes and changes in suicidal behavior (Cleary & Brannik, 2007; Robertson & Cochrane, 1976) and other studies find a negative relationship (Platt, 1989; Sale, Williams, Clark, & Millis, 1975). …”
Section: Discussionmentioning
confidence: 99%
“…Ramstedt [21] and Landberg [18] showed that the strength of the relationship between per capita consumption and a country’s suicidal rate is contingent on the drinking culture. Public attitudes toward suicide in Slovenia are neither permissive nor restrictive [39], so acute alcohol use may be regarded as a disinhibiting agent that plays a role in increasing suicidal risk by intensifying aggressive behavior and propelling suicidal ideation into action [40]. Beside the disinhibiting effect of alcohol in lower doses, heavy drinking could also trigger episodes of depression [40] and interrupt social ties [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the subgroup of respondents with SI they found a tendency towards permissiveness regarding suicide (37). In 2005, Slovene author doctor Andrej Marušič participated in analysis of risk factors for suicide and evidence-based prevention strategies.…”
Section: Suicide In Sloveniamentioning
confidence: 99%